Nanostructured Ternary Metal Tungstate-Based Photocatalysts for Environmental Purification and Solar Water Splitting: A Review - Ke, Jun; Younis, M. Adnan; Kong, Yan; Zhou, Hongru; Liu, Jie; Lei, Lecheng; Hou, Yang (Nano-Micro Letters, 2018)
Visible-light-responsive ternary metal tungstate (MWO4) photocatalysts are being increasingly investigated for energy conversion and environmental purification applications owing to their striking features, including low cost, eco-friendliness, and high stability under acidic and oxidative conditions. However, rapid recombination of photoinduced electron–hole pairs and a narrow light response range to the solar spectrum lead to low photocatalytic activity of MWO4-based materials, thus significantly hampering their wide usage in practice. To enable their widespread practical usage, significant efforts have been devoted, by developing new concepts and innovative strategies. In this review, we aim to provide an integrated overview of the fundamentals and recent progress of MWO4-based photocatalysts. Furthermore, different strategies, including morphological control, surface modification, heteroatom doping, and heterojunction fabrication, which are employed to promote the photocatalytic activities of MWO4-based materials, are systematically summarized and discussed. Finally, existing challenges and a future perspective are also provided to shed light on the development of highly efficient MWO4-based photocatalysts. Highlights: 1 A series of ternary tungstate-based photocatalysts and their applications in solar energy conversion and environmental purification are systematically introduced. 2 The relationship between intrinsic structures and unique properties of ternary tungstate-based photocatalysts is discussed and summarized in detail. 3 Various new concepts and innovative strategies are employed to enhance the photocatalytic performance of ternary tungstate-based photocatalysts